Utility of Pulmonary Angiography by 128-Slice Computed Tomographic Scanner in Diagnosis of Tetralogy of Fallot Cases - Abhishek Dwivedi; Ankur Sharma; Rachit Sharma; Prateek Awasthi; Satveer Singh Choudhary (Case Reports in Radiology)
Tetralogy of Fallot (TOF) is a significant cause of cyanotic congenital heart disease (CHD) encountered in childhood with few cases manifesting in adulthood. It has four classical features (ventricular septal defect, overriding of aorta, hypertrophy of right ventricular hypertrophy, and right ventricular outflow tract obstruction), but the clinical presentation and course can be variable. Due to various anatomical variations and complex anatomy, presurgical planning and postoperative follow-up by pulmonary computed tomographic angiography (CTA) have a very important role. With continued technological advances and the availability of 128-slice computed tomographic (CT) scans, they now play an important role in TOF preoperative evaluation and workup, assisting by minimizing routine invasive digital subtraction catheter angiography. The fast scan of a 128-slice CTA with very sensitive detectors is a very useful modality for studying the complex anatomy and variations as well as its utilization for postoperative management. In this article, we report four cases of TOF where we used a 128-slice scan for performing pulmonary angiography (Optima 660, GE 128, 2180 Premier Row, Orlando, FL 32809, U.S.A.) for preoperative diagnosis and management of three cases and work up for revision surgery for an already operated case with a nonfunctional modified Blalock-Taussig shunt with additional lung parenchymal findings simultaneously. This study will explain the advantageous role of the 128-slice CT scanner over the lesser-slice CT scanners with the ability of pulmonary CTA to facilitate accurate diagnosis and postoperative management.